Anticholinergic burden in middle-aged women and recurrent falls in later life: findings from the Aberdeen prospective osteoporosis screening study (APOSS). (May 2020) - Neal, Samuel R.; Wood, Adrian D.; Ablett, Andrew D.; Gregory, Jenny S.; Guillot, Jordan; Macdonald, Helen M.; Reid, David M.; Myint, Phyo K.
Background: Anticholinergic burden (ACB) is a recognised risk factor for falls in older people; however, whether ACB in middle age predicts falls in later life is unknown. Methods: We examined this association in the middle-aged women of the Aberdeen Prospective Osteoporosis Screening Study (APOSS). ACB was calculated at the second health visit (1997–1999, study baseline) using the Anticholinergic Cognitive Burden Scale. Outcomes were incidence of 1 fall and recurrent falls (⩾2 falls) during the 12 months prior to follow up 2007–2011. Multinomial logistic regression analyses adjusted for potential confounders including demographics, comorbidities and falls history. Results: A total of 2125 women mean age (standard deviation [SD]): 54.7 (2.2) years at baseline and 66.0 (2.2) years at follow up were included. Prevalence of baseline ACB score of 0, 1 and ⩾2 was 87.1%, 7.3% and 5.6%, respectively. Compared with no ACB, ACB ⩾2 was associated with recurrent falls in the previous 12 months [adjusted odds ratio (OR): 2.34, 95% confidence interval (CI): 1.31, 4.19] at an average of 11 years after initial exposure. No such association was found for an ACB score of 1. Conclusions: These findings highlight the potential negative effects of anticholinergic medications in middle age. While cautious use of anticholinergic medications is advisable, further longitudinal research should be conducted to confirm these findings before any specific clinical recommendations can be made. Lay summary: Effect of medicines that block the chemical acetylcholine on falls in women in later life In this paper we describe the link between medicines that block the chemical acetylcholine and falls in later life in women. We used data from a large study in Scotland and we found that there may be a link between such medicines and recurrent falls in later life.